THU0505 MUSCULOSKELETAL ULTRASOUND MONITORING DURING MTX TAPERING IN JIA: A PROSPECTIVE BLINDED COHORT STUDY. (2nd June 2020) - Licciardi, F.; Dellepiane, M.; Covizzi, C.; Figus, F.; Azzolin, I.; Montin, D.; Iagnocco, A.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disease in children. Musculoskeletal ultrasound (MSUS) is a reliable tool in the assessment of chronic inflammatory arthropathies. MSUS in JIA has demonstrated a higher sensitivity for detecting synovitis and tenosynovitis as compared to physical examination. The occurrence of subclinical synovitis (Sub-S: MSUS+/ physical examination -) seems more frequent in wrist and foot joints; the clinical significance of Sub-S in real-life practice is still debated. Methotrexate (MTX) is the most widely used first-line DMARD in JIA therapy. Weekly treatment with MTX leads to clinical remission (CR) in 50-70% of patients. After a variable period of CR (usually 6-18 months), MTX is discontinued. Relapse rate after MTX suspension ranges between 40-50%; no predictors of disease flare have been identified so far. Objectives: We designed a cohort study in order to explore if MSUS monitoring during MTX tapering was able to predict disease flare. Methods: JIA patients in CR (as defined by the JADAS score) for at least 12 months were enrolled in the study. Patients at first attempt of suspension (G1) were tapered as follows: 1 week of suspension every 3 weeks for 3 months + 1 dose every 2 weeks for 3 months; if CR persisted, MTX was stopped. Patients who had a previous flare during/after MTX tapering (G2) had a similar tapering schedule but the step with 1 MTX dose every 2 weeks lasted 6 months. All patients underwent a complete MSUS of 48 joints every 3 months; clinicians who performed physical examinations and follow-up were blinded to US findings for the entire study period. Results: 18 consecutive patients were enrolled between April 2018 and September 2019; patients had prevalently oligoJIA (55.5%) and RF- polyJIA (22.2%). Patients had been treated with MTX for 24.7 months (17.7–48.3), CR had been achieved 4.2 months after MTX start; 61.1% were at their first attempt of MTX tapering (G1). Baseline MSUS: at T0 MSUS detected 9/18 patients (50.0%) with Sub-S (MSUS+). Affected sites at T0 were distributed as follows: 4 MCP joints, 9 MTP joints, 1 f-IP joints, 11 knees. No significant differences resulted in comparing demographic and baseline disease features between MSUS- and MSUS+ patients at T0. Follow-up MSUS : 14 patients (77.8%) completed the entire study protocol, 4 patients are still ongoing. 7 patients relapsed: 42.9% during tapering, 1 of them relapsed during a VZV infection and was excluded from further analysis. We considered as Tlast -MSUS the last available MSUS before relapse or final MSUS (i.e. three months after MTX withdrawal) for not-relapsed subjects. At Tlast 8 patients had at least 1 Sub-S. Sub-S per patient at Tlast were more than Sub-S at T0 (2.85 vs 0.53 p=0.03) but the presence of Sub-S was not related with disease flare (50.0 vs 44.4% p=1). MSUS found 27 Sub-S of the small joints (sMSUS): 88.9% were in the feet, they had an OMERACT grading of 1. sMSUS+ patients were older (8.7 vs 3.9, p=0.002) therefore a weight-induced sub-S not related with JIA could be presumed. Kaplan-Meier curves were analyzed comparing MSUS results at T0 and Tlast, both considering all Sub-S and excluding small feet joints (pMSUS). The best performance was achieved with MSUS at Tlast and pMSUS (figure below, p=0.11). Conclusion: Sub-S are present in 50% of patients in clinical remission >12 months. Sub-S in older patients interest often feet small joints; these Sub-S may be of mechanical origin and are not associated with disease flare. Sub-S increase during MTX tapering. Further patients must be enrolled to understand if Sub-S excluding feet small joints may predict disease flare. References: [1]Amendment of the OMERACT US definitions of joints' features in healthy children using the DOPPLER technique . Collado P et al, Pediatr Rheumatol Online J. 2018. [2]Preliminary Definitions for the Sonographic Features of Synovitis in Children. Roth J, et al ; Arthritis Care Res. 2017. Disclosure of Interests: Francesco Licciardi: None declared, Marta Dellepiane: None declared, Carlotta Covizzi: None declared, Fabiana Figus: None declared, Irene Azzolin: None declared, Davide Montin Speakers bureau: Not relevant for the topic, Annamaria Iagnocco Grant/research support from: Abbvie, MSD and Alfasigma, Consultant of: AbbVie, Abiogen, Alfasigma, Biogen, BMS, Celgene, Eli-Lilly, Janssen, MSD, Novartis, Sanofi and Sanofi Genzyme, Speakers bureau: AbbVie, Alfasigma, BMS, Eli-Lilly, Janssen, MSD, Novartis, Sanofi